Diarrhea due to Cyclospora-like organism in an immunocompetent patient - Mairelina Marín-Leonett,1,2 Lourdes Figuera,1 Anaibeth Nessi,2 Carmen Guzmán,2Patricia Torres,3 Linda Genzlinger,3 Geraldine Saavedra,3Mairalina Marín-Leonett,1 Ynés R. Ortega.3 (Journal of Infection in Developing Countries, 2007)
Cyclospora cayetanensis infection continues to be a major cause of diarrhea particularly in immunosuppressed patients. The emergence of new related parasite pathogens, is an issue of public health concern. We report here a case where a Cyclosporalike organism was the cause of diarrhea in an immunocompetent patient from Venezuela.